ZNF804A variants confer risk for heroin addiction and affect decision making and gray matter volume in heroin abusers. (24th February 2015) - Sun, Yan; Zhao, Li‐Yan; Wang, Gui‐Bin; Yue, Wei‐Hua; He, Yong; Shu, Ni; Lin, Qi‐Xiang; Wang, Fan; Li, Jia‐Li; Chen, Na; Wang, Hui‐Min; Kosten, Thomas R.; et al.
Abstract: Drug addiction shares common neurobiological pathways and risk genes with other psychiatric diseases, including psychosis. One of the commonly identified risk genes associated with broad psychosis has been ZNF804A . We sought to test whether psychosis risk variants in ZNF804A increase the risk of heroin addiction by modulating neurocognitive performance and gray matter volume (GMV) in heroin addiction. Using case‐control genetic analysis, we compared the distribution of ZNF804A variants (genotype and haplotype) in 1035 heroin abusers and 2887 healthy subjects. We also compared neurocognitive performance (impulsivity, global cognitive ability and decision‐making ability) in 224 subjects and GMV in 154 subjects based on the ZNF804A variants. We found significant differences in the distribution of ZNF804A intronic variants (rs1344706 and rs7597593) allele and haplotype frequencies between the heroin and control groups. Decision‐making impairment was worse in heroin abusers who carried the ZNF804A risk allele and haplotype. Subjects who carried more risk alleles and haplotypes of ZNF804A had greater GMV in the bilateral insular cortex, right temporal cortex and superior parietal cortex. The interaction between heroin addiction and ZNF804A variants affected GMV in the left sensorimotor cortex. Our findings revealed several ZNF804A variants that were significantly associated with the risk of heroin addiction, and these variants affected decision making and GMV in heroin abusers compared with controls. The precise neural mechanisms that underlie these associations are unknown, which requires future investigations of the effects of ZNF804A on both dopamine neurotransmission and the relative increases in the volume of various brain areas. Abstract : We assessed the association between psychosis risk variants in ZNF804A and heroin addiction in 1, 035 heroin abusers and 2, 887 controls. The genetic effects on neurocognitive performance and gray matter volume were also studied in the subgroups. Our findings revealed several ZNF804A intronic variants were significantly associated with the risk of heroin addiction, and these variants affected decision making and gray matter volume in heroin abusers.